2020
DOI: 10.3390/app10155255
|View full text |Cite
|
Sign up to set email alerts
|

Non-Uniform Temperature Fields and Effects of Steel Structures: Review and Outlook

Abstract: Due to the dynamic coupling effects of solar radiation, longwave radiation, convective heat transfer, shadows, and other factors, the temperature field and effect of steel structures are significantly non-uniform, differing from traditional concepts that regard the temperature variation of steel structures as a slow and uniform progress. This difference can hinder the correct understanding of the thermal behavior of steel structures and ignore some potential safety hazards. This paper provides a review of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 102 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…The maximum temperature difference of approximately 47 • C was determined in the steel girder [33]. Wucheng Xu et al [34] showed that the heat exchange between the different solar radiation components, heat convection and other factors and the boundaries of the steel structures resulted in a significant nonuniform distribution of the temperatures in steel structures. Due to the complexity of the heat exchange phenomena and not applying it accurately, understanding the steel structure thermal actions can be restrained, leading to jeopardizing the structure safety.…”
Section: Experimental and Numerical Thermal Analyses Of Temperature D...mentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum temperature difference of approximately 47 • C was determined in the steel girder [33]. Wucheng Xu et al [34] showed that the heat exchange between the different solar radiation components, heat convection and other factors and the boundaries of the steel structures resulted in a significant nonuniform distribution of the temperatures in steel structures. Due to the complexity of the heat exchange phenomena and not applying it accurately, understanding the steel structure thermal actions can be restrained, leading to jeopardizing the structure safety.…”
Section: Experimental and Numerical Thermal Analyses Of Temperature D...mentioning
confidence: 99%
“…Due to the complexity of the heat exchange phenomena and not applying it accurately, understanding the steel structure thermal actions can be restrained, leading to jeopardizing the structure safety. The study provided a better understanding of the steel structure thermal behaviors and some recommendations to improve the temperature prediction and distribution in steel structures [34]. The continued exposure of steel structures to solar radiation and other thermal loads during construction can lead to nonlinear and complex temperature variations and distributions, which might impact the quality of engineering construction, the accuracy of structural closures [35], and consequently, the safety of the structure [36].…”
Section: Experimental and Numerical Thermal Analyses Of Temperature D...mentioning
confidence: 99%
“…Assuming a sudden rise or drop of ambient temperature happens, the differences in temperature boundaries will cause inhomogeneous temperature change and induce large nonlinear temperature gradients. The nonlinear temperature gradients along the directions of height, the width of the beam, and thickness of plate unquestionably cause significant deformation and stress of temperature under constraints [17][18][19], which threaten the safety and serviceability [11,20] of aqueducts. Thus, the study of thermal stress of an aqueduct is a significant aspect of the design process, and temperature distribution is the prerequisite for stress analysis.…”
Section: Introductionmentioning
confidence: 99%